O arranjo produtivo local de biotecnologia de Belo Horizonte - Minas Gerais - Carrijo, Michelle de Castro (2005)
Faced with a new capitalist reality characterized by processes of financial and productive globalization and trade liberalization associated with the emergence of a technological paradigm based on information and communication technologies (ICT), local productive arrangements (LPAs) become an element key to understanding the positive insertion of micro and small enterprises as important actors in the generation and incorporation of innovations. The spatial and cognitive proximity allows the development of mechanisms of interdependence and interactive learning that enable the use of collective synergies, thus leading to overcoming the disadvantages inherent in size, the establishment of closer cooperative relationships and active participation in the process. Innovative The objective of this paper is to analyze the configuration, the mode of operation, as well as the peculiarities of the biotechnology APL of Belo Horizonte (MG), identifying the characteristics of the agents and the relationships that are established inside them and the way of insertion of the micro. and small businesses in this type of structure. To this end, a theoretical framework on innovations and systems of innovations based on neo-schumpterian fundamentals was developed; an analysis of the competitive pattern of bio-industry in Brazil and worldwide and, finally, an analysis of the data obtained in a recent field research carried out in the Belo Horizonte biotechnology cluster seeking to understand aspects related to technological capacitation; the existence of externalities and cooperative activities; competitiveness; governance structure and obstacles to growth. In general, among the results found, it can be seen that the biotechnology APL of Belo Horizonte resembles an innovative cluster. This is because it is inserted in an advanced technology sector, has high innovative capacity, managerial competence and qualification level of the workforce, as well as a structure in which several support institutions are present, with the State acting as an inductor and promoter. in its formation. However, it does not have all the classic features of an innovative cluster. Close ties of trust and cooperation between agents and relations with the foreign market are still incipient. There are also difficulties regarding the governance of the APL. Everything indicates that this situation is due to the fact that the APL is still in an embryonic stage, which may change from the development of the arrangement itself or through specific actions.